Penguatan Konsep Filosofi Perebutan Tirta Amertha pada Taman di Jalan Ngurah Rai Kecamatan Gianyar, Kabupaten Gianyar, Provinsi Bali - FEBRIYANI, ANAK AGUNG ISTRI MIRAH; UTAMI, NI WAYAN FEBRIANA; SEMARAJAYA, COKORDA GEDE ALIT (Jurnal Arsitektur Lansekap; Vol.3, No.2, Oktober 2017, 2017)
City Park is a park that situated in urban environment. In a wide scale it can anticipate the impacts caused by city development and it can be enjoyed by all citizens of the city. The existence of a city park in Gianyar City is very important. The problems found in Gianyar city park is that the park lack of space function, especially the utilization of social and cultural space. The purpose of this research were to identify the physical, socio-cultural and historical condition of the three parks in Gianyar subdistrict and to plan the appropriate development concept of the site. This research was conducted from September 2016 to February 2017. The method used in this research were field survey method with observation, interview and distribution of questionnaire technique, and also by conducting literature study. Furthermore, data were processed by tabulation method and qualitative descriptive analysis method which refered to the stages of Simonds planning process (1983). The result of this planning was site plan image with the basic concept Tri Hita Karana (THK) concept at Dewa Wisnu Park, Mandara Giri park and Ciung Wanara of Park.